Analysis of the Impact of Green Investment on Corporate Financial Sustainability in West Java - Taswin, Muhammad; Judijanto, Loso; Sudarmanto, Eko; Astuti, Ambar Kusuma (West Science Interdisciplinary Studies, 2023)
This study investigates the impact of green investment on the financial sustainability of companies in West Java, Indonesia, using quantitative analysis of a sample of 100 companies. Descriptive statistics, correlation analysis, and regression analysis were conducted using SPSS version 26 to assess the relationship between green investment and financial indicators, taking into account moderating variables. The results showed a moderate level of green investment among the companies, with a positive correlation between green investment and financial sustainability indicators (ROI, Net Profit Margin) and a negative correlation with Debt to Equity Ratio. Regression analysis confirmed a significant and positive relationship between green investment and financial sustainability, even when accounting for industry type and firm size. These findings contribute empirical evidence supporting the positive relationship between green investment and financial sustainability in the context of businesses in West Java.